Implementation of Hospital Regulations to Protect Vulnerable Patients: A Comparative Study of Indonesia, Malaysia, and Australia - Muammar Fadillah; M. Yamani; Maria Eka Patri; Noor Aziah Mohd Awal; Cameron Stewart (Trunojoyo Madura University, 2026)
Study Objective: The study aims to examine the implementation of Hospital Regulations (HBL) as an internal legal instrument to protect vulnerable groups and to situate Indonesian practices within a comparative framework informed by hospital governance laws in Malaysia and AustraliaMethod/Approach: The research method is normative-empirical and comparative, and is analyzed descriptively and qualitatively.Novelty: This study lies in its address of the patient dimension of vulnerability. Unlike the current HBL approach, which primarily protects medical professionals, it should also protect patients from unfair litigation and institutional harm.Findings: The results indicate that HBL at Gading Medika Hospital has not been implemented optimally as a comprehensive protection instrument for vulnerable groups. Comparison of the Malaysian Private Health Facilities and Services Act 1998 and the Australian National Standards for Safety and Quality of Health Services.Conclusion: To expect a strong HBL that is sensitive to vulnerable groups, it must align with Law No. 17/2023 and be grounded in best practices, which is a prerequisite for ensuring non-discriminatory access, procedural fairness, and institutional accountability in hospital governance in Indonesia